2019
DOI: 10.15694/mep.2019.000010.1
|View full text |Cite
|
Sign up to set email alerts
|

Parental Experiences of Healthcare Education During Critical Illness

Abstract: Aim: To explore parental experiences and perceptions of healthcare education during critical childhood illness.Methods: Thirty-one parents whose children participated in an educational project while in paediatric intensive care were given mixed qualitative and quantitative questionnaires regarding their involvement in education. Seven parents subsequently participated in semi-structured interviews. Inductive thematic analysis was used to interpret the data.Results: 30/31 parents returned completed questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The findings that parents had more comfort with advanced trainees and less comfort with autonomy in complex patient care tasks (eg, giving medical advice vs performing a history) are consistent with nonpediatric studies [ 4 - 7 ]. Some pediatric studies have found that parents are willing to participate in medical education provided it does not compromise their child’s care [ 10 , 20 ]. Concerns about emotional distress or pain may lead parents to refuse any trainee participation [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings that parents had more comfort with advanced trainees and less comfort with autonomy in complex patient care tasks (eg, giving medical advice vs performing a history) are consistent with nonpediatric studies [ 4 - 7 ]. Some pediatric studies have found that parents are willing to participate in medical education provided it does not compromise their child’s care [ 10 , 20 ]. Concerns about emotional distress or pain may lead parents to refuse any trainee participation [ 9 ].…”
Section: Discussionmentioning
confidence: 99%